The Reflection of The Principle of Social Tolerance in Society (Zien Journal of Social Sciences and Humanities, 2021)
Social tolerance is a spiritual factor that helps to maintain a certain qualitative integrity of systems and structures and social subjects and the relationships between them, despite all actions and changes. Social tolerance is manifested through the interdependence of systems in society, the cooperation of different individuals, state and public organizations, families, self-governing bodies, etc., their interdependence and interdependence